Reduced volume of Heschl's gyrus in tinnitus - Schneider, Peter; Andermann, Martin; Wengenroth, Martina; Goebel, Rainer; Flor, Herta; Rupp, André; Diesch, Eugen (NeuroImage (Orlando, Fla.), 2009)
The neural basis of tinnitus is unknown. Recent neuroimaging studies point towards involvement of several cortical and subcortical regions. Here we demonstrate that tinnitus may be associated with structural changes in the auditory cortex. Using individual morphological segmentation, the medial partition of Heschl's gyrus (mHG) was studied in individuals with and without chronic tinnitus using magnetic resonance imaging. Both the tinnitus and the non-tinnitus group included musicians and non-musicians. Patients exhibited significantly smaller mHG gray matter volumes than controls. In unilateral tinnitus, this effect was almost exclusively seen in the hemisphere ipsilateral to the affected ear. In bilateral tinnitus, mHG volume was substantially reduced in both hemispheres. The tinnitus-related volume reduction was found across the full extent of mHG, not only in the high-frequency part usually most affected by hearing loss-induced deafferentation. However, there was also evidence for a relationship between volume reduction and hearing loss. Correlations between volume and hearing level depended on the subject group as well as the asymmetry of the hearing loss. The volume changes observed may represent antecedents or consequences of tinnitus and tinnitus-associated hearing loss and also raise the possibility that small cortical volume constitutes a vulnerability factor.